A cross-sectional survey of medical and other groups’ awareness, perceptions, and willingness to use e-cigarettes during the COVID-19 pandemic - Deng, Ruihang; Yang, Chuang; Yuan, Yifang; Liang, Lifang; Yang, Xin; Wang, Xinyu; Tian, Jiao; Zhang, Yuxin; Wu, Xuekai; Dai, Haiyun (Frontiers in Public Health, 2024)
Background In China, people’s perceptions towards electronic cigarettes during Corona Virus Disease 2019 (COVID-19) pandemic compared with pre-pandemic conditions have not been explored. Exploring the perceptions of medical workers regarding e-cigarettes is crucial, as they serve as a trusted source of information and providers of smoking cessation counselling for smokers. This cross-sectional study was designed to explore the awareness and perceptions of e-cigarettes among Chinese medical and other groups in the context of the COVID-19 pandemic. Methods A cross-sectional survey was performed using an online, anonymous, and self-administered questionnaire. The questionnaire contained sections for collecting participants’ general information and Likert scale questions regarding smoking status, perceptions of e-smoking, attitude, and willingness to use e-cigarettes. The respondents included medical students, clinical doctors, and other occupations. Data analysis was performed using tools such as descriptive analysis, binary logistic regression, and multivariate regression. Results A total of 952 people completed the questionnaire, and 96.54% of them reported to have heard about e-cigarettes. The most common source of information about e-cigarettes was advertising. Notably, 28 of the 116 smokers reported that they had used e-cigarettes. Independent-samples T-tests results showed that medical groups believed e-cigarettes contained tar (p = 0.03). Most of the medical and non-medical participants maintained neutral attitudes towards e-cigarette policies (38.3%) and prices (49.2%) but their views were significantly different (p < 0.001). Multivariate logistic regression indicated that highly educated people had higher knowledge about e-cigarettes relative to those with lower education (undergraduate, OR = 1.848, 95CI% = 1.305–2.616, p = 0.001; master’s degree or doctoral degree, OR = 1.920, 95CI% = 1.230–2.997, p = 0.004). The medical group used fewer e-cigarettes compared to non-medical group (OR = 1.866, 95CI% = 1.185–2.938, p = 0.007), the non-traditional cigarette users showed lower utilization compared to traditional cigarette users (18–40, OR = 4.797, 95CI% = 0.930–24.744, p = 0.061; > 40, OR = 9.794, 95CI% = 1.683–56.989, p = 0.011) and the older adult used fewer than the young (18–40, OR = 4.797, 95CI% = 0.930–24.744, p = 0.061; > 40, OR = 9.794, 95CI% = 1.683–56.989, p = 0.011). Conclusion This study found that individuals tend to hold negative attitudes towards the awareness, perceptions, and willingness to use e-cigarettes. Medical groups are less likely to use e-cigarettes, but misperceptions are still prevalent among them. This calls for additional training for such medical personnel to improve their capacity to provide necessary counselling to smokers. E-cigarettes advertisements were the main source of information for young individuals to learn about e-cigarettes, and hence measures should be taken to restrict exposure of young individuals to e-cigarettes.